2022
DOI: 10.1039/d2fo02199d
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed extract supplementation modulates hepatic lipid metabolism in rats. Implication of PPARβ/δ

Abstract: In mammals, the liver is involved in nutrient metabolism and the regulation of lipid and glucose homeostasis. Multiple studies have described improvements in liver disorders after regular consumption of grape...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The exact mechanism of grape products on liver function is still unclear. However, previous studies showed that grapes can inhibit liver damage via peroxisome proliferator‐activated receptor gamma (PPARγ) (Guisantes‐Batan et al, 2022). The inactivation of PPAR in hepatocytes is associated with an increase in body and liver weight, as well as a decrease in serum AST levels (Mirzaii et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of grape products on liver function is still unclear. However, previous studies showed that grapes can inhibit liver damage via peroxisome proliferator‐activated receptor gamma (PPARγ) (Guisantes‐Batan et al, 2022). The inactivation of PPAR in hepatocytes is associated with an increase in body and liver weight, as well as a decrease in serum AST levels (Mirzaii et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the hepatoprotective role of GSE was suggested based on the results from an in vivo rat NAFLD model, whereby GSE was found to be more effective than metformin [180]. The PPARγ-dependent modulation of hepatic lipid metabolism might be one mechanism underlying the protective effects of GSE on metabolic parameters [188].…”
Section: Vitis Viniferamentioning
confidence: 99%